A case of Diabetes Striatopathy in an Elderly Female - Sah, Kailash; Gurung, Pritam; Chandra, Avinash; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Diabetes Striatopathy , also known as Non-ketotic hyperglycemic hemichorea or Chorea Hyperglycemia Basal Ganglia Syndrome is rare complication of uncontrolled diabetes. This syndrome has been reported more frequently in elderly Asian womenand symptom resolution is typically associated with serum glucose levels and plasma osmolarity normalization. Herein, we report a case of 75 years old female with CAD-TVD, Hypertension & Type -2 Diabetes Milletus under oral hypoglycemic drugs presented with intermittent involantary movement of face and upper limb who was managed for diabetic striatopathy and showed symptomatic improvement in third day of admission.